Inflammatory and Comorbid Features of Patients with Severe Asthma and Frequent Exacerbations - Denlinger, Loren C.; Phillips, Brenda R.; Ramratnam, Sima; Ross, Kristie; Bhakta, Nirav R.; Cardet, Juan Carlos; Castro, Mario; Peters, Stephen P.; Phipatanakul, Wanda; Aujla, Shean; Bacharier, Leonard B.; Bleecker, Eugene R.; et al. (American journal of respiratory and critical care medicine, 2017)
Reducing asthma exacerbation frequency is an important criterion for approval of asthma therapies, but the clinical features of exacerbation-prone asthma (EPA) remain incompletely defined. To describe the clinical, physiologic, inflammatory, and comorbidity factors associated with EPA. Baseline data from the NHLBI Severe Asthma Research Program (SARP)-3 were analyzed. An exacerbation was defined as a burst of systemic corticosteroids lasting 3 days or more. Patients were classified by their number of exacerbations in the past year: none, few (one to two), or exacerbation prone (≥3). Replication of a multivariable model was performed with data from the SARP-1 + 2 cohort. Of 709 subjects in the SARP-3 cohort, 294 (41%) had no exacerbations and 173 (24%) were exacerbation prone in the prior year. Several factors normally associated with severity (asthma duration, age, sex, race, and socioeconomic status) did not associate with exacerbation frequency in SARP-3; bronchodilator responsiveness also discriminated exacerbation proneness from asthma severity. In the SARP-3 multivariable model, blood eosinophils, body mass index, and bronchodilator responsiveness were positively associated with exacerbation frequency (rate ratios [95% confidence interval], 1.6 [1.2-2.1] for every log unit of eosinophils, 1.3 [1.1-1.4] for every 10 body mass index units, and 1.2 [1.1-1.4] for every 10% increase in bronchodilatory responsiveness). Chronic sinusitis and gastroesophageal reflux were also associated with exacerbation frequency (1.7 [1.4-2.1] and 1.6 [1.3-2.0]), even after adjustment for multiple factors. These effects were replicated in the SARP-1 + 2 multivariable model. EPA may be a distinct susceptibility phenotype with implications for the targeting of exacerbation prevention strategies. Clinical trial registered with www.clinicaltrials.gov (NCT 01760915).